CONSTRUCTION AND ANALYSIS OF ANTENNAL cDNA LIBRARY FROM RICE STRIPED STEM BORER, Chilo suppressalis (WALKER) (LEPIDOPTERA: PYRALIDAE), AND EXPRESSION PROFILES OF PUTATIVE ODORANT‐BINDING PROTEIN AND CHEMOSENSORY PROTEIN GENES. Issue 1 (1st February 2015) - Gong, Zhong‐Jun; Liu, Su; Jiang, Yan‐Dong; Zhou, Wen‐Wu; Liang, Qing‐Mei; Cheng, Jiaan; Zhang, Chuan‐Xi; Zhu, Zeng‐Rong; Gurr, Geoff M
<x xml:space="preserve">Abstract</x> In this study, we constructed a high‐quality cDNA library from the antennae of the Chilo suppressalis (Walker) (Lepidoptera: Pyralidae). A total of 1, 235 colonies with inserts greater than 0.7 kb were sequenced and analyzed. Homology searching coupled with bioinformatics analysis identified 15 and 7 cDNA sequences, respectively, encoding putative odorant‐binding proteins (OBPs) and chemosensory proteins (CSPs). A phylogenetic tree of CsupCSPs showed that each CsupCSP has orthologs in Manduca sexta and Bombyx mori with strong bootstrapping support. One CSP was either very specific or more related to the CSPs of another species than to conspecific CSP. The expression profiles of the OBPs and CSPs in different tissues were measured by real‐time quantitative PCR. The results revealed that of the 11 OBP genes, the transcript levels of CsupOBP1, CsupOBP5, and CsupOBP7 were higher in both male and female antennae than those in other tissues. And CsupCSP7 was highly expressed in both male and female antennae. Based on these results, the possible physiological functions of CsupOBPs and CsupCSPs were discussed.